A new species of Pseudophoxinus (Teleostei: Cyprinidae) from Southwestern Anatolia, Turkey - Ekmekçi̇ F. Güler; Atalay, M. Altuğ; Yoğurtçuoğlu, Baran; Turan, Davut; Küçük Fahretti̇n (Zootaxa, 2015)
Pseudophoxinus mehmeti, new cyprinid species from the Alanköy basin in south-western Turkey, is distinguished from all species of Pseudophoxinus in adjacent regions by the combination of the following characters: body slender, its length 1.3–1.5 times its depth; caudal peduncle length 1.6–2.0 times its depth; mouth almost superior, with the tip of the mouth-cleft approximately level with the middle of the pupil; snout with a pointed tip, its length markedly greater than eye diameter; lateral line not complete, with 30–50 perforated scales and 48–60+2 scale rows in lateral series; 11½–13½ scale rows between lateral line and dorsal-fin origin, 3½–5½ scale rows between lateral line and anal-fin origin; dorsal-fin with 6½–7½ branched rays; anal-fin with 6½–7½ branched rays; a distinct black epidermal stripe from eye to caudal-fin base in preserved individuals.